Studying the perceptive and cognitive function under the stress of match in female futsal players - Sepahvand, H.; Pirzad Jahromi, G.; Sahraei, H.; Meftahi, G. H. (Asian Journal of Sports Medicine, 2017)
Background: Many studies have shown that stress adversely effects cognitive function. However, the effect of acute mental stress is not well understood.